Multiculturalism and religious identity: Canada and India - Beaman, Lori G.; Sikka, Sonia (McGill-Queen's University Press, 2014)
How, and to what extent, can religion be included within commitments to multiculturalism? This book addresses this question by examining the political recognition and management of religious identity in Canada and India